Asuhan Keperawatan Anak Pada Pasien Dengan Campak Di Rumah Sakit Aisyiyah Pariaman - Aisyah Aisarah; Prima Yoselina; Reska Handayani; Erpita Yanti (CV. ITTC INDONESIA, 2026)
Measles is a highly contagious acute infectious disease and remains a significant health problem among children, particularly due to low immunization coverage. In 2025, there was an increase in measles cases in Pariaman City, reaching 115 cases, associated with a vaccination coverage rate of only 40%. This study aimed to describe nursing care provided to a child with measles and emphasize the importance of prevention through immunization. The method used was a case study of a 9-year-old child (An. S) who was hospitalized for five days with a diagnosis of measles. Assessment findings revealed major symptoms including high fever, productive cough, maculopapular rash, decreased appetite, and conjunctivitis. Four primary nursing problems were identified: ineffective airway clearance, hyperthermia, impaired skin integrity, and risk of nutritional deficit. Nursing interventions included fever management, airway care, skin care, and nutritional support delivered comprehensively and continuously. Evaluation results showed that all nursing problems were resolved within five days of care. In conclusion, appropriate and comprehensive nursing care significantly improved the patient's condition. Family education and complete immunization are essential measures to prevent measles in children.